COMPARISON OF BODY COMPOSITION IN BOXERS AND WRESTLERS - Gligoroski, Adam; Kamiloski, Toni; Nestorovska, Mihaela; Ristovski, Vangel (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Introduction: Knowledge of body composition components is important information for athletes, especially those competing in weight-restricted sports such as boxing and wrestling. Objective: Comparison of body composition, fat and lean components, in boxers and wrestlers. Material and methods: Twenty [20] athletes, ten boxers and ten wrestlers, participated in this research. Body composition was analyzed by the bioelectrical impedance method using the InBody 720 device. Results: The average age of boxers and wrestlers was 20.8± 4.8 and 22.3± 4.3 years. Height was 183.3± 6.5 cm for boxers and 175.5 ± 7.0 cm and was significantly higher in boxers, as was weight in boxers 84.37 12 kg versus 74.61± 6.01 kg in wrestlers. Lean component, skeletal muscle mass, total water, protein and mineral content were significantly higher in boxers. Fat component, percentage of fat tissue, degree of obesity was insignificantly higher in boxers. BF% in boxers was 14.11 ± 3.2% vs. 13.27± 3.0% in wrestlers (p=0.568). Boxers had a higher basal metabolic rate (BMR) 1918±166.4 versus 1767.33± 126.9 kilocalories. Conclusion: The parameters of bioelectric analysis of body composition showed that all parameters of the pure (fat-free) component were higher in boxers. All obesity parameters were insignificantly lower in wrestlers. Keywords: body composition, bioelectrical impedance, boxers, wrestlers.